Stan umów Unii Europejskiej z otoczeniem międzynarodowym (przykład WNP, państw Afryki i Azji) - Żukrowska, Katarzyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
The paper analyzes solutions used in the process of institutionalization of relations between UE, CIS member states and the states of Asia and Africa. It also analyzes influence of institutionalization of economic cooperation, particularly export and import, on the position of states involved. Different solutions, such as GSTP for least developed countries, are used. Attention is drawn to the asymmetry in trade relations with the less developed countries, which are given preferential access to EU markets. Those solutions are additionally strengthened by financial instruments. It seems that the results of these actions are positive: GNP increase of African states is higher than the GNP increase of EU-27, especially after 2009. The importance of European Commission and EBC is underlined as an important factor that stimulates growth in those countries. Similar cooperation but on different level is also observed in regard to other continents. The cooperation between Asia, Africa and CIS countries is not limited to transfer of funds. It also includes internationalization of contacts and liberalization of trade, services and capital flow as well as cooperation in research and support of economic transformation. The solutions applied are different for each country, however they are based on the same principles.